Modeling agent formations in two-party adversarial crowds : the case of kettling and bodyguard formations - VECTOR ION, POSADAS (Archīum Ateneo, 2015)
This study makes use of an adapted agent-based crowd model that simulates the behavior of two-party adversarial crowds in two real-world scenarios: a kettling (containment) formation of police blocking the passage of a protester crowd; and a leader protec